Implications of Migrant Skills and Knowledge Transfer for Socioeconomic Development in Nepal - Yakha, Kamal Kumar (Humanities and Social Sciences Journal, 2024)
The study looks into how skills and knowledge acquired by Nepali migrant workers shape socioeconomic development upon return, with a focus on returnee migrants in Belbari Municipality, Morang District. Using purposive sampling, data were collected from 275 returnee migrant households through surveys, interviews, key informant interviews, and field observations. The research explores the effectiveness of skill development programs, the use of remittances for business establishment, and broader socioeconomic changes experienced by returnee households. Most migrants were males aged 25-50 years from the Janajati and Brahmin/Chettri communities who had migrated to the Gulf countries and Malaysia for unskilled work in construction and manufacturing. While many invested their earnings in small agricultural enterprises, income levels remained low, averaging below NPR twenty thousand per month. Returnees also faced other challenges: low wages, health problems, and loan burdens. The findings indicate that the initiatives relating to skill development have hardly benefited them, mainly because many migrants do not have opportunities or the necessary government support to apply the skills they acquired abroad. The study has emphasized stronger skill development programs, accessible financial services, and a stable political and economic environment as preconditions for returnees to build sustainable livelihoods, and contribute constructively to local development.